Teater, tid og tendenser - Vedel, Karen; Mølle Lindelof, Anja; Kuhlmann, Annelis (Peripeti, 2022)
Theatre, Time, and Tendencies Contemporary reflections on historical accounts of performing arts in Denmark In this co-authored paper we examine a selection of publications on theatre history from the last hundred years. Our query has focused on their delimitation of the concept of theatre and the relation between a national Danish and a more comprehensive international perspective. On these grounds we discuss the implications of the various historiographical approaches in their different contexts.